"Blessings and Friends and Knowledge": Environmental Motivations for Religious Literacy. Issue 2 (26th March 2021) - Rackley, Eric D.
Abstract: This two-year ethnographic study examines the motivations for religious knowledge development, or religious literacy, embedded in a Latter-day Saint congregation. Qualitative analyses of observations and 29 interviews with nine youth yielded three characteristics of religious environments that motivated youth for religious literacy. When youth felt the influence of the Holy Ghost (spiritual), had strong social bonds with fellow congregants (relational), and were learning important truths about their faith (educative) motivation for religious literacy increased. Absent these influences, motivation waned. This study raises questions about religious learning spaces, youths' experiences within them, and the religiosocial dynamics that influence them.